Plasma C - reactive Protein and Risk of Breast Cancer in two Prospective Studies and a Meta-analysis - Wang, Jun (Cancer Epidemiol Biomarkers Prev, 2015)
BACKGROUND: C-reactive protein has been evaluated as a risk factor for breast cancer in epidemiologic studies. However, results from prospective studies are inconsistent. METHODS: We evaluated the association using pre-diagnostic blood samples in a case-control study nested within the Nurses' Health Study (NHS) and the full cohort of the Women's Health Study (WHS). 943 cases in the NHS and 1919 cases in the WHS contributed to the analysis. Conditional logistic regression and Cox proportional hazards model were used in the NHS and WHS, respectively. We pooled our results with prior prospective studies using random effect meta-analysis. RESULTS: In the NHS, higher CRP levels were associated with a suggestively increased risk of breast cancer (quintile 5 vs. 1: relative risk [RR] = 1.27, 95% confidence interval [CI] = 0.93, 1.73; P(trend) = 0.02); results did not vary significantly by tumor invasiveness or hormone receptor status. However, no association was observed in the WHS for overall risk (quintile 5 vs. 1: RR = 0.89, 95%CI = 0.76, 1.06; P(trend) = 0.38) or by tumor invasiveness or hormone receptor status. The meta-analysis (including 5371 cases from 11 studies) showed a modestly increased risk among women in the highest vs. lowest categories of CRP (RR = 1.26, 95%CI = 1.07, 1.49). CONCLUSIONS: Existing data from prospective studies suggest that CRP, a non-specific marker of inflammation, is modestly positively associated with breast cancer risk. IMPACT: Our findings provide support to the concept that inflammation can influence breast cancer development.